A model for assessing content strategies of political web sites - Hassan, Shahizan; Li, Feng (Universiti Utara Malaysia, 2003)
Despite hundreds of web sites published daily all over the world,to date,there is very little information on how we can evaluating content strategies of political websites by adopting the Attracting, Informing, Positioning, and Delivering (AIPD) approach. Twenty political web sites from four different countries Malaysia,United Kingdom, United States, and Australia, were analysed comprehensively to elicit the AIPD content elements. A total of 51 elements were identified that represent the basis for the content assessment model.